Modernisasi Pertanian dan Reorientasi Tata Ruang: Tinjauan Kritis atas Praktik Pemerintah Mahakam Ulu - Remon, Yusi; Unyang, Stevani; Luhau, Anastasia Hipui; B, Juachar; Hastira, Muh. Fichriyadi; Nurmiyati, Niken (International Journal of Demos (IJD), 2025)
Abstract This study discusses the agricultural modernization strategy carried out by the Mahakam Ulu Regency Government in responding to the challenges of limited space, extreme geographical conditions, and food security in the 3T region. The focus of the study is directed at the development of dryland rice farming and the role of spatial planning policies as development instruments. The approach used is qualitative based on literature studies, with data sources coming from regional policy documents, official reports, and academic literature. The results of the study show that the Mahakam Ulu Government has implemented a number of strategic policies such as protecting agricultural land, providing planting cost assistance, providing agricultural tools and machinery, and building road and bridge infrastructure. All of these interventions are carried out to support accessibility, production efficiency, and the welfare of farmers in border areas. In conclusion, agricultural modernization in Mahakam Ulu is a form of spatial intervention that is not only technical, but also political, with state involvement in directing the use of space in a planned manner. This approach shows a local development model that is adaptive, contextual, and oriented towards sustainability and spatial justice. Keywords: Modernization, Agriculture, Spatial Planning, Dry Land Rice. Abstrak Penelitian ini membahas strategi modernisasi pertanian yang dilakukan oleh Pemerintah Kabupaten Mahakam Ulu dalam menjawab tantangan keterbatasan ruang, kondisi geografis ekstrem, dan ketahanan pangan di wilayah 3T. Fokus kajian diarahkan pada pengembangan pertanian padi lahan kering dan peran kebijakan tata ruang sebagai instrumen pembangunan. Pendekatan yang digunakan adalah kualitatif berbasis studi kepustakaan, dengan sumber data berasal dari dokumen kebijakan daerah, laporan resmi, dan literatur akademik. Hasil kajian menunjukkan bahwa Pemerintah Mahakam Ulu menerapkan sejumlah kebijakan strategis seperti perlindungan lahan pertanian, pemberian bantuan biaya tanam, penyediaan alat dan mesin pertanian, serta pembangunan infrastruktur jalan dan jembatan. Seluruh intervensi ini dilakukan untuk mendukung aksesibilitas, efisiensi produksi, dan kesejahteraan petani di wilayah perbatasan. Kesimpulannya, modernisasi pertanian di Mahakam Ulu merupakan bentuk intervensi spasial yang tidak hanya teknis, tetapi juga politis, dengan keterlibatan negara dalam mengarahkan pemanfaatan ruang secara terencana. Pendekatan ini menunjukkan model pembangunan lokal yang adaptif, kontekstual, dan berorientasi pada keberlanjutan serta keadilan spasial. Kata kunci: Modernisasi, Pertanian, Tata Ruang, Padi Lahan Kering.